2003
DOI: 10.1063/1.1560876
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric field effect in epitaxial LaVO3/(Ba,Sr)/TiO3/(Pb,La)(Zr,Ti)O3/(La,Sr)CoO3 heterostructures

Abstract: A ferroelectric field effect was demonstrated in epitaxial LaVO3/(Ba,Sr)TiO3/(Pb,La)(Zr,Ti)O3/(La,Sr)CoO3 semiconductor–ferroelectric–metal heterostructures grown on (001) SrTiO3 single crystal substrates by pulsed laser deposition. A high degree of c-axis orientation and strong in-plane texture measured by four-circle x-ray diffractometer confirmed the epitaxial crystallographic relationships between the layers. A 30 nm interlayer of (Ba,Sr)TiO3 was required to prevent decomposition of the (Pb,La)(Zr,Ti)O3 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, when a positive voltage is applied, the polarization vector points to the ZnO layer, accumulating electrons in the semiconductor. In this case, no capacitance other than that contributed by the ferroelectric layer exists and a higher total capacitance is expected . Nevertheless, the higher capacitance under a positive voltage in Nb:STO/BCZT/ZnO/Au heterostructure as compared to Nb:STO/BCZT/Au structure is due to low barrier height and width at the BCZT/ZnO interface, due to charge accumulation, as compared to the BCZT/Au interface under positive-bias condition.…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, when a positive voltage is applied, the polarization vector points to the ZnO layer, accumulating electrons in the semiconductor. In this case, no capacitance other than that contributed by the ferroelectric layer exists and a higher total capacitance is expected . Nevertheless, the higher capacitance under a positive voltage in Nb:STO/BCZT/ZnO/Au heterostructure as compared to Nb:STO/BCZT/Au structure is due to low barrier height and width at the BCZT/ZnO interface, due to charge accumulation, as compared to the BCZT/Au interface under positive-bias condition.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Choi et al have shown that the contribution of the depletion region to the capacitance decreases with the enhancement of charge carriers in a MFS structure, making the C – E curves similar to the one of a MFM structure. Therefore, the 22% capacitance decrease under a negative bias is due to the development of the depletion region in ZnO . Because ZnO is a n-type semiconductor, the majority carriers are electrons; when a negative voltage is applied to the bottom electrode, the polarization vector in the ferroelectric layer points toward the bottom electrode.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar C-V curves were reported in PZT/ LCMO 3 and ͑Pb, La͒͑Zr, Ti͒O 3 / LaVO 3 systems. 13 When N a =1 ϫ 10 17 cm −3 ͑W max ϳ 156 nm͒, C total decreases by ϳ62% under positive voltages in Fig. 4͑d͒, indicating a strong dependence of C total on N a .…”
mentioning
confidence: 87%
“…In some cases, the measured C-V curve of the MFS structure exhibited the typical butterfly shape observed in a metalferroelectric-metal ͑MFM͒ capacitor. 3,4,13 However, in other cases, the shape of C-V curves was so asymmetrical that neither the MFM nor the MFIS model could adequately describe its behavior. [6][7][8] Furthermore, lack of quantitative understanding precluded the C-V measurement of the oxide heterostructure from providing valuable insight into the electrical properties, such as the carrier concentration in the semiconducting oxide, the width of a depletion layer, or the density of interface traps.…”
mentioning
confidence: 99%